1992
DOI: 10.1007/bf02920592
|View full text |Cite
|
Sign up to set email alerts
|

Effects of natural polymer acetylation on the anaerobic bioconversion to methane and carbon dioxide

Abstract: The successful production of novel biodegradable plastic copolymers incorporating both synthetic plastic formulations, such as polystyrene, and naturally occurring biodegradable polymer components, such as cellulose, starch, or xylan, requires stable chemical bonding between these polymers. Modification of the natural polymers through acetylation of the available hydroxyl groups permits the formation of appropriate film-forming plastic copolymers. However, modification of natural polymers has been demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 10 publications
0
26
1
2
Order By: Relevance
“…Rivard et al in 1992 [7] studied CA of increasing DS (0.82-2.4) by incubating them with a special culture for a period of 98 days, and found that CA of DS \1.25 were significantly degraded. The samples with DS [1.7 were also degraded, but to a lesser extent.…”
Section: Biological Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…Rivard et al in 1992 [7] studied CA of increasing DS (0.82-2.4) by incubating them with a special culture for a period of 98 days, and found that CA of DS \1.25 were significantly degraded. The samples with DS [1.7 were also degraded, but to a lesser extent.…”
Section: Biological Degradationmentioning
confidence: 99%
“…Later the importance of the deacetylation step was shown, when it was learned that acetyl esterase enzymes are common in microorganisms. Currently CA is generally recognized as a biodegradable polymer within the scientific community [4][5][6][7][8]. Recent work has allowed a considerable increase in the knowledge of the enzymology of non-substituted and acetylated polysaccharides, thus illuminating the biodegradation mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…However, surprisingly, the 4 and 120 h enzymatic digestibilities of Table II. However, it can be hypothesized that possible cellulose acetylation due to presence of acetyl groups and methylation from 4-Dmethyl glucuronic acid on the xylan backbone during pretreatment and/or residual xylan (<2 wt%) could result in less reactive cellulose, as it is well known that cellulose methylation and acetylation retards cellulase activity (Rivard et al, 1992). solids resulting from pretreatment of cellulose mixed with xylan or xylose were still considerably lower than digestion of cellulose that was pretreated alone at the same severities (Table II).…”
Section: Digestibility Of Solids Prepared At Low Severity (Negligiblementioning
confidence: 99%
“…Although the 6-7 wt% ash content makes it a significant constituent in commercial beechwood xylan, so little is left following pretreatment (data not shown) that it would be highly unlikely to impact hydrolysis. However, it can be hypothesized that possible cellulose acetylation due to presence of acetyl groups and methylation from 4-Dmethyl glucuronic acid on the xylan backbone during pretreatment and/or residual xylan (<2 wt%) could result in less reactive cellulose, as it is well known that cellulose methylation and acetylation retards cellulase activity (Rivard et al, 1992). Causes for cellulose reduced digestibility at low severity: cellulose acetylation.…”
Section: Digestibility Of Solids Prepared At Low Severity (Negligiblementioning
confidence: 99%
“…Reese 2) has reported that several cellulolytic microorganisms such as Pestalotiopsis westerdijkii QM 381 produced cellobiose octaacetatease, which deacetylated cellobiose octaacetate and water-soluble CA (DS, 0.76). It has been reported that CA membranes (DS, 2.5 and 2.8) were degraded by some microorganisms 3) and CAˆl ms (DS, 1.7 and 2.5) were degraded by Pseudomonas paucimobilis 4) , activated sludge, [5][6][7][8] and Bacillus sp. S2055.…”
mentioning
confidence: 99%